The Impact of Sustainable Supply Chain Management and Supply Chain Collaboration on Turkish Firms Performance: Moderator Effect of Uncertainty - Huseyin Ince; Andac Sahinbe Ozkan; Salih Zeki Imamoglu (European Scientific Journal, ESJ, 2020)
Supply Chain-Related Sustainability Cases offer organizations the challenge of enriching environmental, social, and economic performance within supply networks. Firms are increasingly implementing environmental and social dimensions of sustainability. During the implementation, they check the collaboration efforts for getting information outside of the organizations to develop and improve both firm and supply chain performance. Due to drastic changes in the business environment, firms face uncertainty. This study aims to analyze the impact of sustainable supply chain management and collaboration under the supply chain uncertainty on firms' performance. Based on the literature review the conceptual framework was developed. To test the research hypotheses, multi-item scales and survey questionnaires were adopted from prior research. The research is based on a quantitative approach using a questionnaire survey. We obtained 240 usable questionnaires from 112 companies. The Partial Least Square method was used to test the proposed conceptual model. The results show that sustainable supply chain management is positively associated with supply chain performance and supply chain collaboration. Also, we found that supply chain collaboration has a positive effect on supply chain performance. Supply chain performance is positively associated with firm performance. Furthermore, supply chain uncertainty moderates the relationship between collaboration, sustainable supply chain management, and supply chain performance.